2020
DOI: 10.1002/app.50353
|View full text |Cite
|
Sign up to set email alerts
|

Practical two‐step chain extension method to prepare sulfonated waterborne polyurethanes based on aliphatic diamine sulphonate

Abstract: We reported a novel synthesis route to fabricate sulfonated aliphatic waterborne polyurethane dispersions (SWPU) only based on 2‐[(2‐aminoethyl) amino] ethane sulphonate sodium (AAS‐Na) by two‐step chain extension method with the assistance of acetone and water cosolvent. When AAS‐Na was added, only less than 50% of AAS‐Na was incorporated into polyurethane chain in the first‐step chain extension and the residual AAS‐Na formed molecular aggregates which were insoluble in acetone due to the high polarity of AAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Si−OH vibration appeared at 952 cm −1 , and Si− O−Si stretching vibration appeared at 800 cm −1 , while the related intensity peaks of N−H (3327 cm −1 ) and C�O (1705 cm −1 ) were markedly weakened. 44 After the fiber membrane was treated with superhydrophobicity (Figure 4e FTIR spectrum, which also confirmed that the SiO 2 particles were all around the surface of the fiber membrane. 4i).…”
Section: Morphologies and Structures Of Pu/44′-mdi Nanofibrous Membranesmentioning
confidence: 54%
See 1 more Smart Citation
“…Si−OH vibration appeared at 952 cm −1 , and Si− O−Si stretching vibration appeared at 800 cm −1 , while the related intensity peaks of N−H (3327 cm −1 ) and C�O (1705 cm −1 ) were markedly weakened. 44 After the fiber membrane was treated with superhydrophobicity (Figure 4e FTIR spectrum, which also confirmed that the SiO 2 particles were all around the surface of the fiber membrane. 4i).…”
Section: Morphologies and Structures Of Pu/44′-mdi Nanofibrous Membranesmentioning
confidence: 54%
“…Figure e-III shows the FTIR spectrum of the PU/4,4′-MDI- 0.4 /APTES- 2 fiber membrane. Si–OH vibration appeared at 952 cm –1 , and Si–O–Si stretching vibration appeared at 800 cm –1 , while the related intensity peaks of N–H (3327 cm –1 ) and CO (1705 cm –1 ) were markedly weakened . After the fiber membrane was treated with superhydrophobicity (Figure e-IV), the characteristic peaks of Si–OH and Si–O–Si groups were markedly enhanced.…”
Section: Resultsmentioning
confidence: 96%
“…FTIR is a conventional technique to describe the development of important polymeric linkage. Particularly, it is used to observe the development of urethane linkage in the case of PU [43][44][45]. Some of the important linkages are provided in Table 1.…”
Section: Confirmation Of Linkages Of Pu Composites By Ftir Analysismentioning
confidence: 99%
“…Considering viscosity control of the prepolymer, the temperature of prepolymer is usually higher than 45 °C in industrial production, and the R value of the prepolymer process is usually ≥2, which is much different from the acetone method, meaning there will be amount of active NCO groups in prepolymer. After dispersion step, it is the most important issue to control the extremely fast chain-extension reactions between NCO groups and NH 2 groups [ 25 , 26 ]. It is well known that the reactivity of the NCO group toward NH 2 is very high especially when the temperature is above 40 °C and the NCO group concentration is high, which has a high possibility of leading to emulsification failure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the reactivity of the NCO group toward NH 2 is very high especially when the temperature is above 40 °C and the NCO group concentration is high, which has a high possibility of leading to emulsification failure. Molecular weight of polyurethane increases via the formation of urea linkages with NCO-terminated prepolymers and diamines in the chain extension step [ 25 , 27 ]. Therefore, for the prepolymer method, prepolymerization process is easy to control and not a difficulty, the emulsification and amine chain extension stage is difficult to control [ 28 ] because of the above reasons, which directly determines whether the emulsion can be obtained or not.…”
Section: Introductionmentioning
confidence: 99%